Acute seizures predict epilepsy after childhood stroke. Issue 2 (24th September 2013) - Fox, Christine K.; Glass, Hannah C.; Sidney, Stephen; Lowenstein, Daniel H.; Fullerton, Heather J.
<x xml:space="preserve">Abstract</x> Objective To determine incidence rates and predictors of epilepsy after childhood stroke and compare these to published estimates of 3 to 5% cumulative epilepsy incidence by 5 years poststroke in adults. Methods In a retrospective population‐based study of children with stroke (29 days–19 years) in an integrated health care system (1993–2007), poststroke seizures were identified through electronic searches and confirmed by chart review. Stroke and seizure characteristics were abstracted from medical records. Survival analysis was used to determine rates and predictors of remote seizures and active epilepsy (anticonvulsant treatment for remote seizure within prior 6 months) at last follow‐up. Results From a population of 2.5 million children, we identified 305 stroke cases. Over a median follow‐up of 4.1 years (interquartile range = 1.8–6.8), 49 children had a first unprovoked remote seizure. The average annual incidence rate of first remote seizure was 4.4% (95% confidence interval [CI] = 3.3–5.8) with a cumulative risk of 16% (95% CI = 12–21) at 5 years and 33% (95% CI = 23–46) at 10 years poststroke. The cumulative risk of active epilepsy was 13% (95% CI = 9–18) at 5 years and 30% (95% CI = 20–44) at 10 years. Acute seizures at the time of stroke predicted development of active epilepsy (hazard ratio = 4.2, 95% CI = 2.2–8.1). At last follow‐up, ⅓ of the children with active epilepsy had a recent breakthrough seizure despite anticonvulsant usage. Interpretation Unlike adults, children are uniquely vulnerable to epilepsy after stroke. Children with acute seizures at the time of stroke are at particularly high risk. Ann Neurol 2013;74:249–256